Preliminary Report on the Researches at Hazār Sum (Samangan. Italian Archaeological Mission in Afghanistan). Part II (a) Schematic Figurations on the Walls of the Cave Dwellings at Hazār Sum - Castaldi, Editta (1963)
ersch. 1964; I = 26:d:1509.